Heat storage alloy material as well as preparation method and application thereof
By adding an appropriate amount of rare earth element RE to the aluminum-silicon alloy, a heat storage alloy material composed of Al7SiREx chemical composition is formed, which solves the performance decay of aluminum-silicon phase-change heat storage materials in repeated cycles and high temperature environments, and achieves high thermal conductivity and Effects of antioxidant properties.
Patent Information
- Application Number
- CN202411572904.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The thermal properties of aluminum-silicon phase-change heat storage materials decline after repeated melting and solidification cycles, and the oxidation rate increases in high-temperature environments, affecting their use efficiency and service time.
The thermal storage alloy material composed of Al7SiREx chemically is used to control the molar coefficient of the rare earth element RE within the range of 0
The high thermal conductivity, excellent cyclic thermal conductivity and good oxidation resistance of the heat storage alloy material are achieved, extending the service life of the material and reducing production costs.
Smart Images

Figure CN119392047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat storage alloy material and a preparation method and application thereof. Background Art
[0002] With the massive consumption of non-renewable energy, the development and utilization of new energy has become a research focus. The heat storage system can solve the intermittent problem of solar energy, avoid fluctuations in power output, and improve the effective utilization of solar energy. At present, aluminum silicon alloy (Al-Si) has received widespread attention among metal-based phase change heat storage materials due to its low price and high phase change latent heat. The thermal conductivity of aluminum silicon alloy determines the heat transfer efficiency of the material during the phase change process. The greater the thermal conductivity of aluminum silicon alloy, the higher the internal energy transfer efficiency of the material, and the lower the risk of problems such as increased flow resistance at the solid-liquid interface and uneven melting. Aluminum silicon alloys with high thermal conductivity can achieve more melting, solidification, absorption and release cycles in the same time.
[0003] However, there are two problems with aluminum-silicon phase change heat storage materials in actual application environments, which affect their efficiency and service life. On the one hand, after repeated melting, solidification, heat absorption and release cycles, the thermal properties of aluminum-silicon phase change heat storage materials will decline; on the other hand, the operating temperature of aluminum-silicon phase change heat storage materials is about 600°C. The high temperature environment significantly increases the oxidation rate of aluminum-silicon alloys, the oxide layer structure becomes loose, and unstable oxidation occurs as the heating time increases. These will affect the promotion of aluminum-silicon phase change heat storage materials in engineering applications.
[0004] Studies have found that adding trace amounts of Er to Al-12Si, Al-14Si, and Al-16Si alloys can refine the primary Si phase in these alloys and generate Er2Al3Si2 intermetallic compounds. 13 Cu3Ni2Mg 0.5 The alloy caused the eutectic Si phase to be refined from coarse flakes or needles to a fibrous structure, and the average secondary dendrite spacing of the alloy was reduced by 64.6% compared with the original alloy. 20 In the alloy, the primary Si phase can be induced to refine from polygonal star shape to fine block. These studies mainly involve the grain refinement of aluminum-silicon alloys with high Si content.
[0005] CN103451489A discloses a rare earth element samarium alloyed aluminum-silicon alloy, wherein the weight percentages of the components are: silicon is 9.0-9.8%, samarium is 0.05-0.4%, and the balance is aluminum. After heating the Al-Si alloy in a graphite crucible until it is melted, samarium or aluminum-samarium master alloy is added at a temperature of 770-790°C according to the above weight percentages, and the temperature is kept for 5-8 minutes; the alloy melt is subjected to an ultrasonic wave with an intensity of 10-38w / cm2 , intermittent ultrasonic treatment is applied under the conditions of a total ultrasonic treatment time of 3 to 8 minutes, an ultrasonic treatment time of 20 to 30 seconds each time, and an intermittent time of 20 to 30 seconds; then the alloy melt is cooled to 720 to 740°C, kept warm for 31 to 180 minutes, and then solidified at a cooling rate of 40 to 65°C / min. The Si content of the aluminum silicon alloy is relatively low, and its purpose is to improve the mechanical properties of the resulting alloy. In addition, the volatility of samarium alone during the smelting process is relatively high, and the method requires a narrow temperature window and a complex addition procedure to introduce samarium during the smelting process. The price of samarium is very high, which significantly increases the production cost.
[0006] CN110358950A discloses a method for modifying a hypoeutectic cast aluminum-silicon alloy. The raw material formula is as follows: Si: 6.000-12.600%; Sr: 0.001-0.150%, La or RE: 0.020-0.122%, B: 0.001-0.150%, and the Sr / B mass ratio is not greater than 1.351, and the La / B or RE / B mass ratio is between 1 and 5; the remainder is Al. After melting, refining, degassing, feeding and heat-insulating casting, aluminum-silicon alloy is obtained by smelting and casting. The modification grade is 4-6 and the modification effective period is 2-3 hours. This method does not involve the problem of heat storage. The modifier of this method contains Sr, which is relatively expensive, and the dosage ratio of Sr and B needs to be controlled.
[0007] CN114561562A discloses a method for treating AlSi7 alloy, comprising the following steps: mixing Al powder and Ti powder and pressing a blank, pressing the blank and a pure rare earth La block into aluminum liquid, stirring and melting, and casting to obtain an Al-Ti-La master alloy; stirring and heat-insulating the hypoeutectic AlSi7 alloy and the Al-Ti-La master alloy, degassing and removing impurities from the melt, cooling and casting the melt, and obtaining a refined AlSi7 alloy. This method uses the Al-Ti-La master alloy as a modifier to treat the AlSi7 alloy to improve the mechanical properties of the cast Al-Si alloy, such as strength and elongation. The mechanism of action is to promote the transformation of eutectic silicon into fine particles. The essence is a refinement mechanism, and does not involve the heat storage problem of the Al-Si alloy. Summary of the invention
[0008] In view of this, one object of the present invention is to provide a heat storage alloy material having high thermal conductivity, excellent cyclic thermal conductivity and oxidation resistance. Another object of the present invention is to provide a method for preparing the above heat storage alloy material. Another object of the present invention is to provide the use of the above heat storage alloy material as a heat storage material.
[0009] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0010] On the one hand, the present invention provides a heat storage alloy material, the chemical composition of which is Al7SiRE x ;
[0011] Wherein, RE is selected from at least one of La, Ce, Y, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, and Lu;
[0012] x is the molar coefficient of RE, 0<x≤0.2.
[0013] According to the heat storage alloy material of the present invention, preferably, RE is selected from at least one of La, Ce, Y, Pr, Nd, Tb, and Dy; 0.02≤x≤0.15.
[0014] According to the heat storage alloy material of the present invention, preferably, RE is selected from at least one of La, Ce, Pr, and Nd; 0.05≤x≤0.1.
[0015] On the other hand, the present invention also provides a method for preparing the above heat storage alloy material, comprising the following steps:
[0016] 1) providing alloy raw materials according to the molar ratio of Al, Si and RE; the alloy raw materials are composed of Al-Si master alloy and Al-RE master alloy, or the alloy raw materials are composed of pure aluminum, Al-Si master alloy and Al-RE master alloy;
[0017] 2) heating the Al-Si master alloy or the pure aluminum and the Al-Si master alloy at 650-850° C. for 0.5-3 hours to obtain a molten master alloy; adding the Al-RE master alloy to the molten master alloy, heating at 600-800° C. for 10-60 minutes to obtain a heat storage alloy material.
[0018] According to the preparation method of the present invention, preferably, the mass fraction of Si in the Al-Si master alloy is 10-40wt%.
[0019] According to the preparation method of the present invention, preferably, the mass fraction of Si in the Al-Si master alloy is 15-30wt%.
[0020] According to the preparation method of the present invention, preferably, the mass fraction of RE in the Al-RE master alloy is 5-20wt%.
[0021] According to the preparation method of the present invention, preferably, the mass fraction of RE in the Al-RE master alloy is 8-18wt%.
[0022] In another aspect, the present invention also provides the use of the above heat storage alloy material as a phase change heat storage material.
[0023] According to the use of the present invention, preferably, the average thermal conductivity of the heat storage alloy material at 25°C is at least 158 W·m -1 ·K -1 , the average value of the thermal diffusivity is at least 68 mm 2 ·s -1 ;
[0024] The heat storage alloy material has a unit area oxidation weight gain of at most 3×10 -3 g cm -2 , the oxidation rate is at most 2.5×10 -5 g cm -2 ·h -1 .
[0025] The heat storage alloy material of the invention has high thermal conductivity and excellent cyclic thermal conductivity and oxidation resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The X-ray diffraction spectrum of the heat storage alloy material prepared in Comparative Example 1 of the present invention;
[0027] Figure 2 The X-ray diffraction spectrum of the heat storage alloy material prepared in Example 1 of the present invention;
[0028] Figure 3 This is the X-ray diffraction spectrum of the heat storage alloy material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0030] The "thermal conductivity" mentioned in the present invention refers to the amount of heat transferred through an area of 1 square meter in 1 second when the temperature difference between the two sides of a 1 meter thick material is 1°C under stable heat transfer conditions, and the unit is W·m -1 ·K -1 .
[0031] The "thermal diffusion coefficient" mentioned in the present invention refers to the measure of the rate at which the temperature disturbance at one point in an object is transferred to another point, and the unit is mm 2 ·s -1 .
[0032] The "specific heat capacity at constant pressure" mentioned in the present invention refers to the heat required to raise the temperature of a unit mass of a substance by 1K under constant pressure, usually denoted as Cp, with a unit of J·g -1 ·K -1 .
[0033] The "latent heat of fusion" mentioned in the present invention refers to the heat absorbed or released when a substance changes from solid to liquid or from liquid to solid after being heated to its melting point, and the unit is J / g.
[0034] The "oxidation rate" mentioned in the present invention refers to the amount of a substance oxidized per unit time, with the unit of g·cm -2 ·h -1 .
[0035] The “flash point number” mentioned in the present invention refers to a point formed when a beam of light pulse emitted by a laser source irradiates the surface of a sample during the test process of the laser thermal conductivity meter.
[0036] <Heat Storage Alloy Materials>
[0037] The heat storage alloy material of the present invention contains an alloy material of Al and Si. The heat storage alloy material can be used for phase change heat storage, and can also be used for other aspects. The heat storage alloy material can exist in a block, granular or powdered form. If used for heat storage, a block alloy is preferably used.
[0038] The chemical composition of the heat storage alloy material of the present invention is Al7SiRE x The subscripts represent the molar coefficients. x is the molar coefficient of RE. The molar ratio of Al to Si is 7:1.
[0039] According to one embodiment of the present invention, RE can be selected from at least one of La (lanthanum), Ce (cerium), Y (yttrium), Pr (praseodymium), Nd (neodymium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), and Lu (lutetium); preferably, RE is selected from at least one of La (lanthanum), Ce (cerium), Pr (praseodymium), and Nd (neodymium); more preferably, RE is selected from at least one of La (lanthanum) and Ce (cerium).
[0040] According to another embodiment of the present invention, the molar coefficient x of RE may be 0<x≤0.2; preferably 0.02≤x≤0.15; more preferably 0.05≤x≤0.1.
[0041] Controlling the rare earth element ratio within the above range is conducive to inducing the formation of high-density short rod-shaped twins in the Al-Si alloy, improving the thermal conductivity of the heat storage alloy material, and improving the heat storage performance and oxidation resistance of the heat storage alloy material. The lower rare earth addition amount in the present invention forms a submicron solid solution RE (AlSi) compound in the alloy system, which can avoid slag formation and precipitation phase problems during the smelting process, and reduce the overall process complexity and production cost.
[0042] <Preparation method>
[0043] The method for preparing the heat storage alloy material comprises a step of providing raw materials and a step of heating, which is described in detail below.
[0044] Raw material supply steps
[0045] The required alloy raw materials are provided according to the molar ratio of Al, Si and RE.
[0046] According to one embodiment of the present invention, the alloy raw material may consist of Al-Si master alloy and Al-RE master alloy, or may consist of pure aluminum, Al-Si master alloy and Al-RE master alloy.
[0047] The present invention can use any type of Al-Si master alloy and Al-RE alloy. The present invention can use only Al-Si master alloy and Al-RE master alloy, or can add pure aluminum. Preferably, the present invention uses pure aluminum, Al-Si master alloy and Al-RE master alloy. This is conducive to improving the heat storage performance and oxidation resistance of the heat storage alloy material.
[0048] According to one embodiment of the present invention, the mass fraction of Si in the Al-Si master alloy may be 10 to 40 wt %, preferably 15 to 30 wt %, and more preferably 20 to 25 wt %.
[0049] According to another embodiment of the present invention, the mass fraction of RE in the Al-RE master alloy may be 5 to 20 wt %, preferably 8 to 18 wt %, and more preferably 10 to 15 wt %.
[0050] The pure aluminum, Al-Si master alloy and Al-RE master alloy used in the present invention can be commercially available products or prepared by existing preparation methods, and are not particularly limited here. The purity of the pure aluminum, Al-Si master alloy and Al-RE master alloy of the present invention is at least industrial purity (99.9wt%).
[0051] Heating steps
[0052] The Al-Si master alloy or pure aluminum and the Al-Si master alloy are heated for the first time to obtain a molten master alloy; the Al-RE master alloy is added to the molten master alloy and heated for a second time to obtain a heat storage alloy material.
[0053] According to one embodiment of the present invention, the temperature of the first heating may be 650-850°C, preferably 660-820°C, and more preferably 690-810°C.
[0054] According to another embodiment of the present invention, the first heating time may be 0.5 to 3 hours, preferably 0.8 to 2.5 hours, and more preferably 1 to 2 hours.
[0055] According to one embodiment of the present invention, the temperature of the second heating may be 600-800°C, preferably 650-720°C, and more preferably 660-700°C.
[0056] According to another embodiment of the present invention, the second heating time may be 10 to 60 minutes, preferably 15 to 50 minutes, and more preferably 20 to 40 minutes.
[0057] When preparing the heat storage alloy material, the present invention heats the material twice to adjust the phase structure, which is more conducive to inducing the generation of high-density short rod-shaped twins in the heat storage alloy material.
[0058] The present invention can adopt the medium frequency casting method, high frequency arc melting method or belt throwing method, preferably the medium frequency casting method or high frequency arc melting method, more preferably the medium frequency casting method. This is conducive to improving the heat storage performance and oxidation resistance of the heat storage alloy material.
[0059] When heating in the present invention, the alloy raw material can be placed in a vessel, and the alloy raw material is heated together with the vessel. The vessel can be any heating vessel known in the art, and is not particularly limited here. For example, it can be a high-temperature resistant metal mold or crucible; preferably, it can be one of a copper mold, a graphite crucible, a porcelain crucible, and a quartz crucible; more preferably, it can be one of a copper mold of Φ50mm×50mm and a graphite crucible.
[0060] Reasonable heating temperature combined with the composition of alloy raw materials is more conducive to inducing the formation of high-density short rod-shaped twins in heat storage alloy materials, improving the thermal conductivity of heat storage alloy materials, and improving the heat storage performance and oxidation resistance of heat storage alloy materials. At the same time, it can shorten the heating time and save production costs. Too low temperature will reduce the fluidity of the alloy melt and inhibit the formation of twins. Too high temperature will cause the size of eutectic silicon in the alloy melt to become smaller, which will also inhibit the formation of twins.
[0061] <Purpose>
[0062] The present invention also provides the use of the heat storage alloy material.
[0063] In the present invention, the heat storage alloy material can be used as the phase change heat storage material.
[0064] In the present invention, the average value of the thermal conductivity of the heat storage alloy material at 25°C is at least 158 W·m -1 ·K -1 , preferably at least 160 W·m -1 ·K -1 , more preferably 160 to 180 W·m -1 ·K -1 .
[0065] In the present invention, the average value of the thermal diffusion coefficient of the heat storage alloy material at 25°C is at least 68 mm 2 ·s -1 , preferably at least 70 mm 2 ·s -1 , more preferably 70 to 80 mm 2 ·s -1 .
[0066] In the present invention, the heat storage alloy material has a unit area oxidation weight gain of at most 3×10 -3 g cm -2 , preferably at most 2.5×10 -3 g cm -2 , more preferably 1.5 to 2.5 × 10 -3 g cm -2 The oxidation rate of the heat storage alloy material under 96 hours of high temperature oxidation conditions is at most 2.5×10 -5 g cm -2 ·h -1 , preferably at most 2.4×10 -5 g cm -2 ·h -1 , more preferably 2 to 2.4×10 -5 g cm -2 ·h -1 .
[0067] The heat storage alloy material of the present invention has high thermal conductivity, excellent cyclic thermal conductivity and oxidation resistance, and is particularly suitable as a heat storage material in a high temperature range of 600°C.
[0068] <Test method>
[0069] Thermal Cycle Test Method
[0070] Weigh 20g of alloy sample, polish the sample surface with sandpaper, and place them in alumina crucibles. To avoid oxidation during the experiment, the thermal cycle experiment was carried out in a vacuum tube furnace. According to the binary alloy phase diagram, the solidus temperature of Al7Si alloy is 577±1℃. To ensure complete melting and solidification of the alloy, the upper limit melting temperature and lower limit solidification temperature of the thermal cycle were selected in this experiment, which were 67℃ higher and lower than the solidus temperature, that is, Al7SiLa x The thermal cycle temperature range of the alloy is 510~644℃.
[0071] The thermal cycle test program is set as follows: first heat the alloy sample at 700°C for 0.5 hours to fully melt the alloy sample, then heat it at 510°C for 0.5 hours to start the thermal cycle program. Heat to 644°C at a rate of 5°C / min, heat for 0.5 hours, then cool to 510°C at a rate of 5°C / min, and heat for half an hour. The thermal cycle program is a cycle from heating to 644°C to cooling to 510°C. The number of thermal cycle experiments is 100. After 100 thermal cycles, the alloy sample is taken out of the alumina crucible and cut at the center of the alloy sample for alloy structure detection and heat storage performance detection.
[0072] High temperature oxidation resistance test method
[0073] Before the experiment begins, place the empty alumina crucible used to hold the alloy in a box-type resistance furnace and heat it at 600°C for 3 hours to remove excess water from the alumina crucible to ensure that the mass of the alumina crucible does not change. Clean the alumina crucible with alcohol, and record the mass of the alumina crucible after the alcohol evaporates completely. Weigh 20g of the alloy sample, polish the surface of the alloy sample to remove the surface oxide scale, and then weigh it, and record the total mass of the alloy sample and the alumina crucible.
[0074] The high-temperature oxidation resistance experiment was carried out in a box-type resistance furnace, and the weight gain method was used to determine the performance of the oxide film. The alumina crucible containing the alloy sample was placed in the furnace, and the experimental temperature was set to 700°C. The timing started after the furnace temperature reached the set temperature, and the alloy samples were taken out after heating for 24, 48, 72, and 96 hours, respectively. The alloy sample needs to be cooled to 470°C in the furnace with the furnace (to ensure the solidification of the alloy and prevent operating errors when taking out the crucible and spilling of the alloy liquid). After the alloy sample is cooled, the alloy sample and the alumina crucible are immediately weighed and recorded. Then, the isothermal oxidation kinetic curve is drawn based on the data to detect the increase of the oxide film on the alloy surface.
[0075] Other test methods in the following examples and comparative examples are described as follows:
[0076] XRD pattern: detected and produced using D / MAX2500V X-ray diffractometer.
[0077] Thermal diffusivity and thermal conductivity: tested using LFA 467 laser thermal conductivity instrument from NETZSCH Group, Germany.
[0078] Latent heat of fusion: Detected by STA449 F3 synchronous thermal analyzer from NETZSCH Group, Germany.
[0079] <Ingredients>
[0080] The raw materials in the following examples are all commercially available products unless otherwise specified.
[0081] Comparative Example 1
[0082] Pure aluminum and Al-Si master alloy (Si is 20 wt%) are weighted according to the molar ratio of Al and Si in the chemical composition of Al7Si (i.e. Al7SiLa0).
[0083] After pure aluminum and Al-Si master alloy are placed in a graphite crucible, the graphite crucible is placed in a medium frequency induction furnace and heated at 750° C. for 1 hour to obtain a heat storage alloy material with a chemical composition of Al7Si.
[0084] The obtained heat storage alloy material was subjected to X-ray diffraction detection and X-ray diffraction detection was prepared. The XRD results are shown in Figure 1 .Depend on Figure 1 It can be seen that the Al phase and Si phase compositions (XRD-copper target) of the heat storage alloy material of Comparative Example 1 correspond to standard cards PDF 00-004-0787 and PDF 00-027-1402, respectively.
[0085] The obtained heat storage alloy material was subjected to a thermal cycle test, and the results are shown in Table 1; and the thermal diffusion coefficient and thermal conductivity of the heat storage alloy material were tested, and the results are shown in Table 2.
[0086] Table 1
[0087]
[0088] Table 2
[0089]
[0090] It can be seen from Table 1 and Table 2 that the average thermal conductivity of the heat storage alloy material of Comparative Example 1 obtained by testing at room temperature (25°C) is 155.3 W·m -1 ·K -1 The average thermal diffusion coefficient reaches 65.9 mm 2 ·s -1 Under 100 thermal cycles at 600°C, its latent heat of fusion decreased from 330.7 J / g to 315.2 J / g, with a loss rate of 4.68%.
[0091] The obtained heat storage alloy material was subjected to a high temperature oxidation resistance test. The results of the oxidation weight gain per unit area are shown in Table 3, and the results of the oxidation rate are shown in Table 4.
[0092] Table 3
[0093]
[0094] Table 4
[0095]
[0096] It can be seen from Table 3 and Table 4 that the heat storage alloy material of Comparative Example 1 has a unit area oxidation weight gain of 3.908×10 -3 g cm -2 , and its oxidation rate is 4.07×10 -5 g cm -2 ·h -1 .
[0097] Example 1
[0098] Pure aluminum, Al-Si master alloy (Si is 20wt%) and Al-La master alloy (La is 10wt%) are prepared according to the chemical composition of Al7SiLa 0.06 The molar ratio of Al, Si and La in the alloy is balanced.
[0099] Pure aluminum and Al-Si master alloy were placed in a graphite crucible, and the graphite crucible was placed in a medium frequency induction furnace and heated at 750°C for 1 hour to obtain a molten master alloy. Al-La master alloy was added to the molten master alloy and heated again at 680°C for 30 minutes to obtain a master alloy with a chemical composition of Al7SiLa 0.06 Heat storage alloy material.
[0100] The obtained heat storage alloy material was subjected to X-ray diffraction detection, and the XRD results are shown in Figure 2 .Depend on Figure 2 It can be seen that the heat storage alloy material of this embodiment is composed of Al phase, Si phase and La (AlSi) compound phase (XRD-copper target), corresponding to standard cards PDF00-004-0787, PDF 00-027-1402 and PDF 97-060-8329-1402 respectively.
[0101] The obtained heat storage alloy material was subjected to a thermal cycle test, and the results are shown in Table 5; and the thermal diffusion coefficient and thermal conductivity of the heat storage alloy material were tested, and the results are shown in Table 6.
[0102] Table 5
[0103]
[0104] Table 6
[0105]
[0106]
[0107] It can be seen from Tables 5 and 6 that the average thermal conductivity of the heat storage alloy material obtained in this embodiment is 179.2 W·m-1 ·K -1 The average value of thermal diffusion coefficient reaches 70.1mm 2 ·s -1 Under the condition of 100 times of 600℃ thermal cycle, its melting latent heat is reduced from 312.6J / g to 304.6J / g, and the loss rate is only 2.5%. Compared with the data of the heat storage alloy material of comparative example 1, the heat storage alloy material of this embodiment has high thermal conductivity, excellent cyclic thermal conductivity and high temperature thermal cycle stability.
[0108] The obtained heat storage alloy material was subjected to a high temperature oxidation resistance test. The results of the oxidation weight gain per unit area are shown in Table 7, and the results of the oxidation rate are shown in Table 8.
[0109] Table 7
[0110]
[0111] Table 8
[0112]
[0113] It can be seen from Tables 7 and 8 that the heat storage alloy material obtained in this embodiment has a unit area oxidation weight gain of 2.285×10 -3 g cm -2 , and its oxidation rate is 2.38×10 -5 g cm -2 ·h -1 Compared with the data of the heat storage alloy material of Comparative Example 1, the heat storage alloy material of this embodiment has excellent high-temperature oxidation resistance.
[0114] Example 2
[0115] Pure aluminum, Al-Si master alloy (Si is 25wt%) and Al-La master alloy (La is 15wt%) are prepared according to the composition of Al7SiLa 0.1 The molar ratio of Al, Si and La in the alloy is balanced.
[0116] Pure aluminum and Al-Si master alloy were placed in a graphite crucible, and the graphite crucible was placed in a medium frequency induction furnace and heated at 800°C for 2 hours to obtain a molten master alloy. Al-La master alloy was added to the molten master alloy and heated again at 700°C for 35 minutes to obtain a master alloy with a chemical composition of Al7SiLa 0.1 Heat storage alloy material.
[0117] The obtained heat storage alloy material was subjected to X-ray diffraction detection, and the XRD results are shown in Figure 3 .Depend on Figure 3It can be seen that the heat storage alloy material of this embodiment is composed of Al phase, Si phase and La (AlSi) compound phase (XRD-copper target), corresponding to standard cards PDF00-004-0787, PDF 00-027-1402 and PDF 97-060-8329-1402 respectively.
[0118] The obtained heat storage alloy material was subjected to a thermal cycle test, and the results are shown in Table 9; and the thermal diffusion coefficient and thermal conductivity of the heat storage alloy material were tested, and the results are shown in Table 10.
[0119] Table 9
[0120]
[0121] Table 10
[0122]
[0123]
[0124] It can be seen from Tables 9 and 10 that the average thermal conductivity of the heat storage alloy material of this embodiment measured at room temperature (25°C) reaches 161.6 W·m -1 ·K -1 The average value of thermal diffusion coefficient reaches 70.2mm 2 ·s -1 Under the condition of 100 times of 600℃ thermal cycle, its melting latent heat is reduced from 331.2J / g to 289.6J / g, and the loss rate is only 12.5%. Compared with the data of the heat storage alloy material in comparative example 1, the heat storage alloy material in this embodiment has high thermal conductivity and excellent cyclic thermal conductivity.
[0125] The obtained heat storage alloy material was subjected to a high temperature oxidation resistance test. The results of the oxidation weight gain per unit area are shown in Table 11, and the results of the oxidation rate are shown in Table 12.
[0126] Table 11
[0127]
[0128] Table 12
[0129]
[0130] It can be seen from Tables 11 and 12 that the heat storage alloy material obtained in this embodiment has a unit area oxidation weight gain of 1.931×10 -3 g cm -2 , and its oxidation rate is 2.011×10 -5 g cm -2 ·h -1Compared with the data of the heat storage alloy material of Comparative Example 1, the heat storage alloy material of this embodiment has excellent high-temperature oxidation resistance.
[0131] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A heat storage alloy material, characterized in that: Its chemical composition is Al7SiRE x ; Wherein, RE is selected from at least one of La, Ce, Y, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, and Lu; x is the molar coefficient of RE, 0<x≤0.
2.
2. The heat storage alloy material according to claim 1, characterized in that: RE is selected from at least one of La, Ce, Y, Pr, Nd, Tb, and Dy; 0.02≤x≤0.
15.
3. The heat storage alloy material according to claim 2, characterized in that: RE is selected from at least one of La, Ce, Pr, and Nd; 0.05≤x≤0.
1.
4. A method for preparing the heat storage alloy material according to any one of claims 1 to 3, comprising the following steps: 1) providing alloy raw materials according to the molar ratio of Al, Si and RE; wherein the alloy raw materials are composed of Al-Si master alloy and Al-RE master alloy, or the alloy raw materials are composed of pure aluminum, Al-Si master alloy and Al-RE master alloy; 2) heating the Al-Si master alloy or the pure aluminum and the Al-Si master alloy at 650-850° C. for 0.5-3 hours to obtain a molten master alloy; adding the Al-RE master alloy to the molten master alloy, heating at 600-800° C. for 10-60 minutes to obtain a heat storage alloy material.
5. The preparation method according to claim 4, characterized in that: The mass fraction of Si in the Al-Si master alloy is 10-40 wt %.
6. The preparation method according to claim 5, characterized in that: The mass fraction of Si in the Al-Si master alloy is 15-30 wt %.
7. The preparation method according to claim 4, characterized in that: The mass fraction of RE in the Al-RE master alloy is 5-20wt%.
8. The preparation method according to claim 7, characterized in that: The mass fraction of RE in the Al-RE master alloy is 8-18 wt %.
9. Use of the heat storage alloy material according to any one of claims 1 to 3 as a phase change heat storage material.
10. The use according to claim 9, characterized in that The average thermal conductivity of the heat storage alloy material at 25°C is at least 158 W·m -1 ·K -1 , the average value of the thermal diffusivity is at least 68 mm 2 ·s -1 ; The heat storage alloy material has a unit area oxidation weight gain of at most 3×10 - 3 g cm -2 , the oxidation rate is at most 2.5×10 -5 g cm -2 ·h -1 .
Citation Information
Patent Citations
High-temperature antioxidant heat storage aluminum alloy
CN103215479A
Rare earth element ytterbium alloyed aluminum-silicon alloy and preparation method thereof
CN103469026A
High-thermal-conductivity aluminum alloy for radiator and preparation method thereof
CN115821124A
Method for fabrication of high silicon Al-Si alloy forelectronic packaging material by vacuum arc meltingmethod
KR1020040084315A